A triacontanuclear [Zn12Dy18] cluster: a ring of [Dy4] cubes. Issue 2 (30th October 2015) - Stavgianoudaki, Nikoleta; Siczek, Milosz; Lis, Tadeusz; Inglis, Ross; Milios, Constantinos J.
Abstract : A ring of cubes: synthesis and properties of a triacontanuclear [Zn12 Dy18 ] cluster. Abstract : The reaction between Dy(NO3 )3 ·6H2 O, Zn(OAc)2 ·4H2 O, salicylaldehyde and 2-amino-isobutyric acid, in MeOH in the presence of NEt3 under solvothermal conditions, led to the isolation of the triacontanuclear mixed-metal cluster [Zn II 12 Dy III 18 (OH)30 (L)12 (sal)6 (OAc)6 (NO3 )3 (H2 O)6 ](NO3 )3 ·12MeOH·5H2 O (1·12MeOH·5H2 O), which displays frequency- and temperature-dependent out-of-phase magnetic susceptibility signals.